Epicardial cyst—a case report. Issue 4 (July 1972) - Edwards, M. H.; Ahmad, A.
Abstract : The first successful removal of an epicardial cyst is reported. Evidence is presented to demonstrate that the cyst developed as a result of an abnormality occurring within the first five weeks of fetal life.